Oil contracts and government take: Issues for Senegal and developing countries - Bertrand Laporte; Awa Diouf (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
The challenge of developing countries that have natural resources is to attract international investors for the valuation of that wealth and to get a « fair » share of oil revenue. So, the « design » of the oil tax system determines the level of resource exploitation and the oil rent-sharing. The analysis of the Senegal oil tax regime is based on the assessment of oil revenue sharing between the government and the operating companies for a 2014 oil discovery, according to two types of contract: a concession contract and a production sharing contract. Regardless of the contract, average effective tax rates in Senegal are low, compared to other African producer countries, and the taxation regime is regressive. Developing countries must, therefore, be vigilant in defining the applicable tax regime, both for the oil sector and, more generally, for extractive industries. The choice of the production sharing contract is certainly the most widespread, but it does not guarantee either the tax system progressivity or a sufficient government take. The taxation rules that specify the production sharing contract must, therefore, be established by skilfully combining income-based taxes and production-based taxes to define a progressive and sufficiently remunerative tax system for both parties, the state and the investor. The balance between these two types of taxation should be systematically calibrated using a rent-sharing model. For Senegal, in particular, it involves a revision of the oil code in force.
Keywords: 330; extractive industries; oil contract; government take; Senegal; Developing countries